Estudo do processamento de filmes finos nanocristalinos a partir da irradiação de luz ultravioleta de sistemas de nanopartículas - Wilges, Matheus Bittencourt (Universidade Federal de São Carlos, 2023)
In general, nanoceramics are produced from the sintering process of compacted systems of nanometric powders, whose consolidation process is favored by the high surface energy of the nanoparticles. However, such a processing route has important challenges for the production of nanocrystalline materials. Furthermore, and no less challenging, the microstructural control itself during the sintering process of nanoparticles is complex, notably the preservation of the nanometric size of the grains is hampered by the processes of coalescence and grain growth during sintering. Despite the advancement of unconventional sintering processes, such techniques require high investment and increase the complexity of the process. Given this scenario, this work studied the formation of nanocrystalline films of metal oxides (ZrO2 and TiO2) by the consolidation of nanoparticles, without the aid of additional thermal energy (i.e., at room temperature). The films were formed from nanoparticles colloids from the materials under study, deposited on surfaces and consolidation promoted by the removal of ligands from their surfaces by ultraviolet radiation. Thus, the work proposes the formation of nanoceramics (in the form of thin films) using primarily the surface energy of the nanoparticles, without heat treatment, in order to control the growth of the grains and, consequently, preserve the nanostructure
Study of the processing of thin nanocrystalline films using ultraviolet iradiation from nanoparticle systems
Keywords: Filmes finos; Nanopartículas; ZrO2; TiO2; Thin films; Nanoparticles; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS